A test method for predicting the neutron irradiation resistance of aluminum materials

The ion implantation technology is used to simulate neutron radiation damage on aluminum material samples, which solves the problem of difficulty in accurately evaluating the neutron radiation resistance performance of aluminum materials in the existing technology, and achieves high-precision prediction under low-cost and low-radioactivity conditions. .

CN119064258BActive Publication Date: 2025-01-21SHANGHAI NUCLEAR ENGINEERING RESEARCH & DESIGN INSTITUTE CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411571477.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate and predict the radiation resistance of aluminum materials under neutron radiation conditions, and the direct neutron radiation test is high, the time is long and there is a radioactive risk.

Method used

Ion implantation technology was used to simulate neutron irradiation damage on aluminum material samples. Solid element ions, gaseous element ions and heavy ion injection were used to simulate solid transmutation damage, gas transmutation damage and detachment damage respectively, and through nanohardness testing and micro-radiation Evaluate based on signs of damage.

Benefits of technology

It achieves accurate simulation and prediction of neutron radiation damage to aluminum materials without using high-cost and highly radioactive neutron irradiation conditions, and improves the prediction accuracy of neutron radiation resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119064258B_ABST
    Figure CN119064258B_ABST
Patent Text Reader

Abstract

A test method for predicting the neutron irradiation resistance of aluminum materials belongs to the field of radiation-resistant materials: providing aluminum material samples and off-site damage dose targets of target test areas, calculating the atomic concentration of elements produced by transmutation according to the off-site damage dose targets; injecting solid element ions to simulate solid transmutation damage, injecting gaseous element ions to simulate gas transmutation damage, injecting heavy ions and passing the heavy ions through the target test area to simulate off-site damage; cutting cross-sectional samples of the target test area for nanohardness testing and microscopic irradiation damage statistics, and predicting the damage behavior of aluminum materials under the same neutron irradiation according to the statistical results. This method does not require the use of a neutron source, and can accurately simulate off-site damage, solid transmutation damage, gas transmutation damage and their synergistic effects, thereby improving the accuracy of predicting the neutron irradiation resistance of aluminum materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of radiation-resistant materials, and in particular relates to a test method for predicting the neutron radiation resistance performance of aluminum materials. Background Art

[0002] Aluminum and its alloys have good thermal conductivity, processability, mechanical properties and neutron economy, and have been widely used in the field of nuclear power. However, aluminum materials will experience a variety of radiation damage mechanisms such as ex situ damage, solid transmutation damage and gas transmutation damage under neutron irradiation conditions, resulting in significant degradation of their performance. Therefore, accurate evaluation and prediction of the neutron irradiation resistance of aluminum materials is of great significance to the safety of nuclear power facilities. Due to the long time and high cost of direct neutron irradiation tests and the strong radioactivity in the test process, it is difficult to carry out large-scale tests on aluminum materials. Therefore, providing a test method that can accurately simulate and predict the neutron irradiation resistance of aluminum materials under real conditions is of positive significance for improving the safety performance of aluminum structural parts of nuclear power facilities. Summary of the invention

[0003] The purpose of the present invention is to provide a test method for predicting the neutron irradiation resistance performance of aluminum materials, so as to improve the accuracy of predicting the neutron irradiation resistance performance of aluminum materials.

[0004] According to an embodiment of the present invention, a test method for predicting the neutron irradiation resistance of aluminum materials is provided, the method comprising the following steps:

[0005] Step a): providing an aluminum material sample, determining a target test area and an off-site damage dose target in the aluminum material sample, and calculating the atomic concentration of the element produced by transmutation in the target test area;

[0006] Step b): respectively performing solid element ion implantation, gaseous element ion implantation and heavy ion implantation on the target test area; wherein the ion implantation parameters of the solid element and the gaseous element are determined according to the atomic weight of the element produced by the transmutation calculated in step a); the implantation parameters of the heavy ion are determined according to the off-situ damage dose target, so that the heavy ion forms off-situ damage in the target test area and is deposited outside the target test area;

[0007] Step c): Cut a cross-sectional sample of the target test area, and perform nanohardness testing and microscopic radiation damage characterization on the cross-sectional sample.

[0008] After pure aluminum and aluminum alloy materials are subjected to neutron irradiation, ex-situ damage, solid transmutation damage and gas transmutation damage will occur inside. Without using high-cost and high-radioactivity neutron irradiation, these three types of damage need to be accurately simulated. Among them, under real neutron irradiation conditions, solid transmutation damage is mainly caused by Al atoms capturing neutrons and transmuting to produce Si isotopes, gas transmutation damage is caused by neutron irradiation to produce H and He isotopes aggregated to form bubbles, and ex-situ damage is caused by Al atoms in the lattice being collided with neutrons and leaving their original positions. In the above method, ion implantation technology is used to simulate three different neutron irradiation damages separately: solid transmutation damage is simulated by injecting Si ions into the target test area; gas transmutation damage is simulated by injecting H and He ions into the target test area; ex-situ damage is simulated by injecting heavy ions into the test area, and the energy of heavy ions is controlled to make the heavy ions deposit outside the test area to avoid becoming impurities. Microscopic characterization of the test area where simulated neutron irradiation damage was formed makes it possible to predict the behavior of aluminum materials under neutron irradiation conditions.

[0009] Furthermore, in some embodiments, in step a), the aluminum material sample is configured as a polished aluminum material sheet, and the distance between the target test area and the surface of the aluminum material sample is not less than 200nm. The test area should be at a certain depth from the sample surface to avoid the influence of surface effects on the test results; at the same time, the depth range of the test area should be able to allow solid element ions and gaseous element ions to be deposited in it within an appropriate energy range, while heavy ions can pass through completely.

[0010] Furthermore, in some embodiments, in step b), the solid element is Si, and the gaseous element is H and He. In other embodiments, when the element composition in the aluminum alloy produces other transmutation elements, other solid or gaseous element ions may also be added.

[0011] Furthermore, in some embodiments, in the step b), the heavy ions are configured as Au ions or I ions.

[0012] Further, in some embodiments, in the step b), for the angle α between the ion implantation direction and the surface normal of the aluminum material sample, α1>α2>α3, wherein α1 is the angle of the solid element ions, α2 is the angle of the gaseous element ions, and α3 is the angle of the heavy ions. The incident angles of the solid element ions and the gaseous atomic ions are reasonably selected by calculation so that the gaseous element ions and the solid element ions can be deposited together in the test area.

[0013] Further, in some embodiments, in step b), α1 = 60°, α2 = 20°, and α3 = 0°. Heavy ion injection along the normal direction of the sample surface can achieve the maximum penetration depth and avoid remaining in the test area.

[0014] Furthermore, in some embodiments, in the step b), the energy of Si ions is 500keV-800keV, the energy of H ions and He ions is 40keV-80keV, and the energy of the heavy ions is at least 3MeV.

[0015] Furthermore, in some embodiments, in the step b), before ion implantation, at least 3000 ion implantation simulation calculations are performed for each type of ion.

[0016] Furthermore, in some embodiments, in the step c), the nanohardness test is performed using a nanoindenter.

[0017] Furthermore, in some embodiments, in the step c), the method for counting microscopic irradiation damage comprises: performing transmission electron microscopy analysis on the cross-sectional sample, and performing electron energy loss spectrum analysis and X-ray energy spectrum analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a flow chart of an experiment for predicting the neutron irradiation resistance of aluminum materials in one embodiment;

[0019] Figure 2 is an off-site damage and ion concentration distribution curve simulated by SRIM program in one embodiment;

[0020] Figure 3 This is a TEM photo of a sample cross section in one embodiment;

[0021] Figure 4 The nanohardness distribution curve of the sample cross section in one embodiment and the comparative sample.

[0022] The purpose of the above drawings is to explain the present invention in detail so that those skilled in the art can understand the technical concept of the present invention, but it is not intended to limit the present invention. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The phrase appearing in various locations in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive independent or alternative embodiments. Those skilled in the art should be able to understand that the embodiments herein may be combined with other embodiments without causing structural conflicts.

[0025] In the description of this document, terms indicating orientation or positional relationships, such as "up", "down", "left", "right", "horizontal", "vertical", "height", "length", and "width", are intended to accurately describe the embodiments and simplify the description, but are not intended to limit the parts or structures involved to have a specific orientation, be installed or operate in a specific orientation, and should not be construed as a limitation on the embodiments in this document.

[0026] In the description of this article, the terms "first", "second" and the like are only used to distinguish different objects, and cannot be understood as indicating relative importance or limiting the quantity, specific order or primary and secondary relationship of the described technical features. In the description of this article, the meaning of "plurality" is at least two.

[0027] As aluminum materials (aluminum and aluminum alloys) are increasingly used as structural materials in the neutron irradiation environment of nuclear power plant containment, accurate evaluation of the neutron irradiation resistance of aluminum materials is of great significance to the safety of nuclear power facilities. However, due to the high cost of neutron sources and the radioactive hazards, the time and economic costs of testing the neutron irradiation resistance of aluminum materials in a real neutron irradiation environment are unbearable.

[0028] At present, in some schemes, the use of energetic ion irradiation tests to simulate neutron irradiation effects has attracted attention due to its advantages of fast speed, low cost and non-radioactivity. There are two main types of ion irradiation schemes for aluminum materials: one is self-ion irradiation based on aluminum ions. Since the ion type is consistent with the main component of aluminum materials, the influence of other foreign elements as impurities can be avoided as much as possible; the other is the use of heavier ion irradiation such as gold and iron. Due to the stronger interaction with aluminum materials during irradiation, higher irradiation doses can be achieved in a shorter time. However, under real neutron irradiation conditions, the damage mechanism in the aluminum material matrix is ​​very complex: in addition to the ex situ damage caused by neutrons directly hitting Al atoms, Al atoms will also capture neutrons and transmute into Si isotopes, thereby forming solid transmutation damage; at the same time, the transmutation of nuclides under neutron irradiation will also release gaseous hydrogen isotopes or helium isotopes, which will gather in the aluminum material matrix to form bubbles, forming gas transmutation damage. There is a synergistic damage effect among the three types of damage, namely, ex-situ damage, solid transmutation damage, and gas transmutation damage. This makes it impossible for existing heavy ion irradiation technology solutions to accurately simulate the neutron irradiation damage behavior of aluminum materials, and therefore it is difficult to accurately predict the neutron irradiation resistance of aluminum materials.

[0029] In order to solve the above problems, an embodiment of the present invention provides a test method for predicting the neutron irradiation resistance of aluminum materials, which accurately simulates the neutron irradiation damage of aluminum materials through multi-ion beam irradiation tests, thereby improving the prediction accuracy of the neutron damage resistance of aluminum materials.

[0030] like Figure 1 As shown, the method comprises the following steps:

[0031] Step a): Provide an aluminum material sample. In different embodiments, the aluminum material can be pure aluminum or an aluminum alloy, depending on the object of analysis. Define a target test area in the aluminum material sample, determine the off-site damage dose target based on the service conditions of the aluminum material parts, and calculate the solid and gaseous element atomic concentrations generated by transmutation in the target test area based on the off-site damage dose.

[0032] Specifically, in a preferred embodiment, the calculation process may use the SRIM program to determine the physical parameters such as the delocalization threshold and surface binding energy of each element in the aluminum material with reference to the recommended standard in ASTM E521-16, and determine the atomic number level of the transmuted element under a given delocalization damage dose target.

[0033] The aluminum material sample is prepared by cutting a large piece of aluminum material into a suitable size, and in a preferred embodiment, cutting it into thin sheets, grinding and polishing the sample surface to a mirror surface to eliminate the interference of macro fluctuations on the test results; then performing vibration polishing to eliminate surface stress.

[0034] In a preferred embodiment, the distance between the target test area and the surface of the aluminum material sample is not less than 200 nm, so that the depth range falls within the range of solid element ions and gaseous element ions while eliminating the interference of surface effects.

[0035] Step b): Solid element ions, gaseous element ions and heavy ions are injected into the target test area. In a preferred embodiment, Si ions are used as solid element ions to simulate solid transmutation damage, H ions and He ions are used as gaseous element ions to simulate gas transmutation damage, and heavy ions are used to impact Al atoms in the matrix to simulate ex-situ damage. The SRIM program can be used to calculate the range depth of Si ions, H / He ions and heavy ions with different energies in aluminum materials, and the energy of different ions is selected according to the ion accelerator parameters used in the test; then the ex-situ damage caused by various ions incident on aluminum materials at the selected energy and the spatial distribution of the ions themselves are further calculated, and finally the required dose level is determined according to the neutron irradiation state to be simulated, thereby determining the energy and injection amount of each ion. In order to make the results statistically significant, before conducting the ion implantation test, simulation calculations of no less than 3,000 ion implantations should be performed for the solid element ions, gaseous element ions and heavy ions to be injected.

[0036] In a preferred embodiment, attention should be paid to the geometric relationship between the incident directions of the three beams of Si ions, H / He ions and heavy ions. The angle between the incident direction and the normal line of the sample surface is α, then α1>α2>α3, where α1 is the angle of solid element ions, α2 is the angle of gaseous element ions, and α3 is the angle of heavy ions. The larger α is, the greater the thickness of the material that the incident ions pass through when reaching the same depth. In the experiment, it is necessary to make the solid element ions and gaseous element ions co-deposit in the selected target test area, and make the heavy ions pass through the target test area as a whole and deposit in the deep area of ​​the sample far away from the target test area. In a further preferred embodiment, α1=60°, α2=20°, α3=0°, that is, the heavy ions are injected perpendicular to the sample surface so that the heavy ions can completely pass through the target test area. Heavy ions should be selected from elements with large atomic numbers that do not react with aluminum materials, such as Au ions or I ions.

[0037] In a preferred embodiment, the energy of Si ions is set to 500keV-800keV, the energy of H ions and He ions is set to 40keV-80keV, and the energy of heavy ions is at least 3MeV.

[0038] In a preferred embodiment, the temperature and beam intensity are accurately monitored during ion irradiation, and the level of injection is determined by calculating the beam intensity and the accumulated irradiation time. The temperature detection is mainly achieved by arranging thermocouples inside the sample stage, on the surface of the sample stage, or on the surface of the irradiated sample; the beam current detection is mainly achieved by measuring the total beam current intensity reaching the sample surface through a Faraday cup, and then calculating it based on the actual area of ​​the irradiated sample. In a further preferred embodiment, the beam current intensity ratio of solid element ions, gaseous element ions, and heavy ions remains unchanged during the test.

[0039] Step c): Microscopic characterization of the target test area.

[0040] Cut a cross-sectional sample containing the target test area. In some embodiments, this can be done by using a focused ion beam (FIB) device and referring to the lift-out standard process to prepare a sample suitable for transmission electron microscopy (TEM) analysis. When using FIB to prepare a cross-sectional sample, it is necessary to first spray C or Pt elements on the sample surface to protect the irradiated surface from being damaged. At the end of the FIB process, a low-energy ion beam of 5keV or 2keV is used to clean both sides of the sample to remove the damaged layer caused by high-energy ion beam thinning. The thickness of the FIB sample does not exceed 100nm.

[0041] In other embodiments, a thin slice may be prepared by wire cutting or the like and then further prepared as a TEM sample by electrolytic double spraying or ion thinning technology.

[0042] Specifically, nano-hardness tests were performed on cross-section samples using a nano-indenter; the distribution of defects such as dislocations and voids was analyzed in TEM characterization, and the sample thickness was determined using electron energy loss spectroscopy (EELS) to statistically analyze the number density of microstructures such as voids, dislocations, and precipitates; the composition of the precipitate was analyzed using an X-ray energy dispersive spectrometer (EDS), and the structure and type of the precipitate was determined in combination with electron diffraction patterns. Each sample was subjected to at least 25 nano-indentation tests, with the spacing between adjacent indentations being no less than 50 μm.

[0043] In a preferred embodiment, the test is carried out with the goal of predicting the neutron irradiation resistance of an aluminum alloy during service in a certain type of reactor. Under given service conditions, the off-site damage dose target is 100 dpa, and under neutron irradiation conditions, the transmutation generation rate of Si element is about 130 appm / dpa, the transmutation generation rate of H element is about 1.5 appm / dpa, and the transmutation generation rate of He element is about 0.3 appm / dpa.

[0044] Considering factors such as surface effects, the depth range of 300nm-600nm from the sample surface was taken as the target test area.

[0045] Conduct ion irradiation experiment design.

[0046] First, the range distribution of Si ions with different energies in the aluminum alloy is calculated, and the appropriate injection energy is selected based on the performance parameters and working conditions of the multi-beam ion irradiation device actually used. In this embodiment, 800keV Si ions are selected and injected at a 60° angle to the sample surface normal, so that the Si element concentration peak is concentrated in 300nm-600nm and the distribution in this area is relatively uniform. According to the transmuted Si element generation rate, the required Si ion injection amount corresponding to 100dpa is calculated to be 3.3×10 16 ions / cm 2 , and finally the average concentration of Si element implanted in the depth range of 300nm-600nm was 1.3at%.

[0047] Then, based on the performance parameters and working conditions of the multi-beam ion irradiation device actually used, it is determined that the heavy ion beam is incident perpendicular to the sample surface, and the H ions and He ions are incident at a 20° angle to the normal on both sides of the surface normal, and the three beams are located in the same plane. Based on the above geometric relationship, in order to ensure that the peak concentrations of H ions and He ions are concentrated in the range of 300nm-600nm, appropriate H ions with energies of 50keV and He ions with 75keV are selected respectively. According to the transmutation production rates of H and He elements, the required ion injections corresponding to 100dpa are calculated to be 2.5×10 14 ions / cm 2 and 7.5×10 13 ions / cm 2 , so that the average concentrations of H and He elements in the 300nm-600nm region are 150appm and 30appm, respectively. At the same time, appropriate heavy ion species and energy are selected to produce relatively uniform off-site damage in the 300nm-600nm research area and ensure that the heavy ions themselves are deposited away from this area. After comprehensive consideration, 4.5MeV I ions are selected for incidence, with a fluence of 7.7×10 16 ions / cm 2 , producing an average of 100dPa of off-site damage in the range of 300nm-600nm.

[0048] The SRIM program simulates the distribution of Si ions, H / He ions, and ex-situ damage in aluminum alloy samples with depth. Figure 2 shown.

[0049] The aluminum alloy samples treated with ion irradiation were cut and prepared into cross-sectional samples for TEM characterization. Figure 3 As shown in the figure, a large number of cavities (white dots) formed by irradiation can be observed. EELS can be used to count the density of irradiated cavities.

[0050] The nanoindenter was used to test the hardness of the aluminum alloy samples treated with ion irradiation and the control aluminum alloy samples not treated with ion irradiation, and the nanohardness distribution at different depths was obtained, such as Figure 4 As shown, it can be seen that the hardness of the material increases significantly after irradiation.

[0051] According to the above test results, the hardness, defect density and other properties of the aluminum alloy with 100dpa off-site damage under neutron irradiation can be predicted. In other embodiments, the aluminum alloy can also be subjected to gradient simulation tests of different off-site damages, so as to conduct a more comprehensive evaluation of the aluminum alloy's tolerance to neutron irradiation.

[0052] The test method for predicting the neutron irradiation resistance of aluminum materials used in the above embodiment uses Si ion, H / He ion and heavy ion composite ion irradiation to accurately simulate the composite damage caused by neutron irradiation. The test cycle is short, the economic cost is low, and the radioactive risk is small. It is convenient to accurately simulate the irradiation damage behavior of aluminum materials under different neutron irradiation conditions by adjusting the test parameters, thereby improving the research and development speed of nuclear materials and the efficiency of screening and evaluating structural materials under irradiation environments. This method can not only simulate the ex-situ damage caused by neutron irradiation, but also reflect the synergistic effect between ex-situ damage, solid transmutation damage and gas transmutation damage, thereby more accurately predicting the neutron irradiation resistance of aluminum materials.

[0053] The purpose of the above embodiments is to further explain the present invention in detail in conjunction with the accompanying drawings so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the present invention, the optimization or equivalent replacement of the method steps involved, and the combination of the implementation methods in different embodiments without conflict of structure and principle, all fall within the protection scope of the present invention.

Claims

1. A test method for predicting the neutron irradiation resistance of aluminum materials, characterized in that: The following steps are involved: Step a): providing an aluminum material sample, determining a target test area and an off-site damage dose target in the aluminum material sample, and calculating the atomic concentration of the element produced by transmutation in the target test area; Step b): respectively performing solid element ion implantation, gaseous element ion implantation and heavy ion implantation on the target test area; wherein the solid element is configured as Si, and the gaseous element is configured as H and He; The ion implantation parameters of the solid element and the gaseous element are determined according to the atomic concentration of the element produced by the transmutation calculated in step a): the solid element ion implantation amount required in the target test area under the off-site damage dose target is calculated according to the transmutation generation rate of the Si element; the gaseous element ion implantation amount required in the target test area under the off-site damage dose target is calculated according to the transmutation generation rate of the H and He elements; the ion implantation energy and the implantation angle are set so that the solid element and the gaseous element are deposited in the target test area; The implantation parameters of the heavy ions are determined according to the off-situ damage dose target: the type, energy, injection volume and angle of the heavy ions are determined according to the off-situ damage dose target of the target test area, so that the heavy ions form off-situ damage that reaches the off-situ damage dose target in the target test area and are deposited outside the target test area; Step c): Cut a cross-sectional sample of the target test area, perform nanohardness testing and microscopic radiation damage characterization on the cross-sectional sample, wherein the microscopic radiation damage characterization includes determining the spatial distribution of dislocations, voids, and precipitates, determining the thickness of the cross-sectional sample and the number density of dislocations, voids, and precipitates, and determining the structure and type of the precipitates.

2. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1, characterized in that: In the step a), the aluminum material sample is configured as a polished aluminum material sheet, and the distance between the target test area and the surface of the aluminum material sample is not less than 200 nm.

3. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1, characterized in that: In the step b), the heavy ions are configured as Au ions or I ions.

4. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 3, characterized in that: In the step b), for the angle α between the ion implantation direction and the surface normal of the aluminum material sample, α1>α2>α3, wherein α1 is the angle of the solid element ions, α2 is the angle of the gaseous element ions, and α3 is the angle of the heavy ions.

5. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 4, characterized in that: In the step b), α1=60°, α2=20°, and α3=0°.

6. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1, characterized in that: In the step b), the energy of Si ions is 500keV-800keV, the energy of H ions and He ions is 40keV-80keV, and the energy of the heavy ions is at least 3MeV.

7. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1 or 2, characterized in that: In the step b), before ion implantation, at least 3000 ion implantation simulation calculations are performed for each type of ion.

8. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1 or 2, characterized in that: In the step c), the nanohardness test is performed using a nanoindenter.

9. The test method for predicting the neutron irradiation resistance of aluminum materials according to claim 1 or 2, characterized in that: In the step c), the method for counting microscopic irradiation damage includes: performing transmission electron microscopy analysis on the cross-sectional sample, and performing electron energy loss spectrum analysis and X-ray energy spectrum analysis.

Citation Information

Patent Citations

  • Mechanical performance testing method for irradiation material

    CN108827773A

  • Molten salt reactor radial shielding structure and molten salt reactor comprising same

    CN113851233A